Application Of The Goal Programming Method In Increasing Plate Production For Steel Ships - Nurhasanah, Nurhasanah; Septi Ayu Angraini; Romadhoni, Romadhoni (SEAN Institute, 2024)
PT. Gunawan Dianjaya Steel (GDS) is one company that produces steel plates in Indonesia. PT GDS was hot sheet steel factory (BLP ) producing steel and steel in all sorts of different types and design of consumer conformed to order.A kind of steel produced by the blp hot sheet steel it is divided into the type form the coil and plate masing-masing form the quality of being domestic composed of different kinds, imports and CRM. Production planning basically there are three elements need to be considered, the consumers, products, and the manufacturing process.All three of these elements is a very complex to be faced by the company.This study attempts to determine the optimal combination that can reach the whole purpose of these elements of the company. Methods used in this research is goal programming, a method of optimize developed to solve the problems with the aim of more than one.The goal programming has the ability to achieve a number of goals or target. From the mathematical linear fomulasi until they reached the goal total production x1 + x2 + x3 = 10 + 75 + 65 = 140 plate targetless 150 plate.Goal of a production = 10 plate that means 40 plate under production target of 50 plate goal products b = 75 plate that means in accordance with company production target.Goal production products c = 65 plate that means less than 15 a plat of 80 plate company production target.The product is the total second Rp.100.000 x1 + Rp. 175.000 x2 + Rp. 200.000 x3 = Rp.100.000 (10) + Rp.175.000 (75) + Rp.200.000 (65) = Rp. 1.000.000,- + Rp.13.125.000,- + Rp.13.000.000,- = Rp. 27.125.000,-